JU:MP leads: sparking physical activity leadership and supporting positive youth development in a deprived community - Crowther, Jamie; Lever, Elliot; Dogra, Sufyan; Barber, Sally; Hall, Jennifer (Frontiers in Sports and Active Living, 2024)
Physical activity interventions in deprived communities should acknowledge the social, political, and cultural context in which they are delivered. Targeted young leaders programs can harness positive youth development principles and address these concerns by engaging underrepresented young people and developing them as physical activity leaders who can support local delivery efforts. Community-based Youth Leadership development programs are under-researched, and little is known about how to develop young people from deprived communities as physical activity leaders. This research project used iInterviews, focus groups and Ripple Effects Mapping to evaluate a community based young physical activity leaders development program delivered in a community with high levels of deprivation in Bradford, UK. The program, known as ‘JU:MP leads’ developed 20 young people aged 16-25 as young leaders between September 2022 and September 2023. Thematic analysis of data uncovered that a community-based young leaders development program can be effective in supporting local young people from a deprived community to develop as physical activity leaders, particularly when adopting a flexible delivery model through which young people can engage around other commitments. Key mechanisms within the program that supported development included the acquisition of formal, nationally recognised qualifications, informal training and mentorship, peer support and ongoing reflection.These key mechanisms of the program facilitated the personal and professional development of the young people into confident and assured physical activity leaders. The research concluded that community based physical activity leaders programs can support Positive Youth Development of young people from deprived communities by developing their skills and supporting them to make valid contributions to local physical activity provision.